Ecological study of Ghodaghodi lake - Diwakar, J; Barjracharya, S; Yadav, UR (Banko Janakari, 2009)
Wetlands comprise 5% of world's total land areas of Nepal. The present study Ghodaghodi Lake in the Far-West Nepal Terai manifested the physicochemical contamination in the lake. All the parameters were within the WHO guideline values except for Phosphate and Dissolved Oxygen. Water depth varies form 1-4 m. High phosphate level suggested that the lake is hypertrophic. Dissolved oxygen was low, ranging between 5.27-6.56 mg/l. The presence of high density of Hemiptera (384.23 ind/m2) and Ephimeripterae (273.66 ind/ m2) indicted that water was polluted due to high nutrient deposition both from the decaying of the abundant aquatic flora and from the surrounding area. The most important challenge that we have to face is to strike a balance between sustainable human exploitation and maintaining the ecological character of a wetland ecosystem. Key words: Ghodaghodi Lake, phytoplankton, macroinvertebrates, phosphate, nitrate doi: 10.3126/banko.v19i3.2207 Banko Janakari, Special Issue February 2009, 18-23